How social media and technology are challenging journalists' perceptions of their role. Issue 1 (1st July 2019) - Jukes, Stephen
Professional ideology and newsroom culture have become deeply embedded and codified in Anglo-American journalism since the late nineteenth century. Despite constant questioning by professionals and scholars, they have remained stable, resisting the repeated challenge of technological, societal and cultural changes. The antagonism between professional journalists and the boundaries they are erecting to distinguish themselves from 'citizen journalists', or those they regard as 'amateurs', is arguably reinforcing existing ideology. But are there other disruptive factors ushered in by the social media revolution that may finally lead to a breakdown of these norms? Using a qualitative research methodology involving semi-structured interviews with journalists from leading established news outlets, this article examines two changes to practice now becoming commonplace in the newsroom. Firstly, it explores the growing requirement for journalists to use Twitter and other social media tools to promote their own news output or their news organization; and secondly it examines the introduction of social media 'hubs' in which journalists trawl the Internet for user-generated content to complement their own. To what extent are these two developments changing journalists' perception of their role and the culture of the newsroom? And is the broadly consensual view of their professional ideology becoming more diffuse?